(untitled) (Vietnam Journal of Community Medicine, 2024)
Subject and methods: 61 patients over 18 years old with tibial plateau fractures were treated fixation with plate and screws and minimally invasive surgery at Thong Nhat Hospital – Ho Chi Minh city from January 2019 to January 2023, were divided into 2 groups, in which group 1: 30 patients without 3D printing models and group 2: 31 patients with the support of 3D printing models. Results: A mean follow-up time of 13 ± 3.65 months (group 2) and 12.67 ± 3.3 months (group 1), a mean surgical time of group 2 (126.39 ± 40.51minutes) was shorter than group 1 (146.93 ± 38.87 minutes)(P=0.048), mean blood loss of group 2 (341 ± 115.11 ml) was less than group 1 (409.73 ± 114.87 ml)(P=0.044). The results were good to excellent in 100% with a mean Rasmussen score of group 2: 28.35 ± 3.58, there was no difference in age, hospital stay or treatment outcomes between 2 groups, the near complications were superficial wound infection in 3.22% (group 2) and 6.7% (group 1)(P=0.612) of patients, with no deep venous thrombosis or compartment syndrome observed. Long-term complications included mild pain with weather changes and feeling of an implant under the skin in 7/31 (group 2) and 8/30 (group 1) patients.